Problems of Long-Term Therapy of Chronic Diseases: Compliance – Refusal of Therapy – Motivation for Treatment (Texas Journal of Medical Science, 2023)
The article discusses the problem of compliance in terms of treatment of patients with chronic diseases. Lack of adherence to therapy (non-compliance) significantly reduces the effectiveness of treatment, and often negates all the efforts of doctors.